Study on Avian Biodiversity of North-east India with Special Reference to the Conservation of Threatened Species - Upadhyaya, S.; Raj, M. (International Journal of Bio-resource and Stress Management, 2013)
The North-Eastern Region of India, comprising the states of Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram, Nagaland, Tripura and Sikkim is renowned for its immense biodiversity which has made it a priority area for investment by the leading conservation agencies of the world. Most of the north-eastern states have more than 60% of their geographic area under forest cover, a minimum suggested coverage for the hill states in the country. The region which is only 7.76% of the geographic area of the country accounts for nearly 25% of its forest cover. North-East India supports one of the highest bird diversities in the Orient. Of the 1,232 species of avifauna recorded from India, more than 850 bird species record their presence in the north-eastern region of India. The eastern Himalaya and the Assam plains have been identified as an Endemic Bird Area by the Royal Society for the Protection of Birds. The global distribution of 24 restricted-range species is limited to the region. The present paper is an attempt to review the threatened species of birds found in the states of N.E. India and analyze their conservation status vis a vis the recent IUCN Red List, Wildlife Protection Act, CITES and CMS. Efforts taken for conservation of the threatened species of birds in the region are analyzed.